Linguistic Sensitivity in an Inclusive Classroom - Kumari, Sharda (THE PRIMARY TEACHER, 2019)
The general perception of inclusive education being imparted in an educational institution implies is limited to provision of disabled friendly infrastructure to enable differently abled children to move around the premises on their own without any hindrance. However, this approach involves very little focus on the attitude and language of the teachers or the management staff and neither does any systematic orientation exist in this regard. This study is based on an observation undertaken in schools of Delhi as sample where the teachers were observed while teaching in classes sixth, seventh and eight. Their body language and speech were observed in the context to inclusive education.